Topology based modelling of crochet structures. (4th November 2022) - Storck, Jan Lukas; Gerber, Dennis; Steenbock, Liska; Kyosev, Yordan
Crocheted textiles receive scarce scientific study and are at present not produced in automatized industrial scale. Computer-aided modelling and simulation offer capabilities for investigating possible technical fields of application. In this context a novel approach for modelling crocheted textiles consisting of chains, slip stitches and single crochets using a topology based and parameterized key point representation at the meso scale is proposed. According to the stitch size, yarn diameter and pattern spline interpolated models, which are free of interpenetrations up to approximately a 1/10 ratio of yarn diameter to stitch size, are generated by a developed Python program and software from the company TexMind. The models are suitable for finite element method (FEM) applications with LS-DYNA with which the mechanical properties of crocheted textiles can be studied. Exemplary simulations show anisotropic properties and homogeneous distribution of stresses in a crocheted textile. Due to the computationally simple and flexible modelling the presented approach may serve as a tool for designing planar crocheted textiles. This allows for estimation of the required yarn length and offers the prediction capabilities of simple and fast FEM simulations based on beam elements.